Development of Civil Servant Resources at the Silian Raya District Office, Southeast Minahasa Regency - Wanga, Julex; Tumbel, Goinpeace; Langkai, Jeane Elisabeth (Technium Social Sciences Journal, 2021)
This study aims to analyze the development of Civil Servant resources at the Silian Raya District office, Southeast Minahasa Regency. The focus of research in research is the development of Civil Servant resources through a). through education b). training, c) seminars, d). courses, and e). upgrading. Data collection techniques are through: PNS planning documents, observations, and interviews on a). 6 employees of Silian Raya District, b). Section Head, c). Head of Planning Sub Division, d). Secretary to the sub-district head, e). Camat. The results showed that: a). The recruitment pattern for filling positions at the Silian Raya District Office has not been carried out based on the work tasks needed to achieve organizational goals, b. The form of education carried out to improve civil servants' performance is left to the decision of civil servants to develop higher education levels, c). The training provided to civil servants depends on the availability of district government funds. Based on the results of these studies, it is recommended that: a). The recruitment pattern for filling positions at the Silian Raya District Office is based on achieving organizational goals in the District, b). The form of education carried out to improve civil servants' performance is provided in the form of educational scholarships., c). The training provided to civil servants is adjusted to the needs of the work or position held.